Foreign Direct Investment-growth Nexus Revisited: New Evidence from Bangladesh - Begum, Munira; Salahuddin, Mohammad; Chowdhury, Mamta; Wahid, Abu N. M. (International Journal of Economics and Financial Issues, 2018)
Due to mixed empirical findings, FDI-growth nexus is still an issue of debate. This paper estimates the long-run association between FDI and economic growth for Bangladesh using time series data for the period 1985-2014. Results from Dynamic Ordinary Least Squares (DOLS) demonstrate positive and significant long-run relationship between FDI and economic growth. A bidirectional causality also exists between them. The study further indicates that financial development and trade openness also Granger cause economic growth. Variance decomposition analysis results confirm the future positive role of FDI, trade openness and financial development in the context of Bangladesh. Policy implications are discussed. Keywords: Bangladesh, DOLS, economic growth, FDI JEL Classifications: F21, F43